Electrophoretic deposition infiltration of 2-D metal fibre-reinforced cordierite matrix composites of tubular shape - Kaya, C; Kaya, F; Boccaccini, AR (KLUWER ACADEMIC PUBL, 2002)
Stainless steel (316L) fibre mats shaped into tubular geometry were used to reinforce cordierite. The ductile phase-reinforced cordierite matrix composites were manufactured by using electrophoretic deposition (EPD) and pressureless sintering. An EPD cell suitable for the fabrication of tubular composites was designed. The relevant process parameters required to infiltrate the fibre mats with nanosized cordierite powders and to obtain homogeneous electrophoretic cordierite deposits on the inner and outer surfaces of the fibrous substrate were optimised. EPD experiments were conducted under constant voltage conditions (5 V dc) with varying deposition times. The sintered composites having internal and external deposit thickness of about 1 mm were free of surface cracks when a deposition time of 2.5 min was used. The developed metal fibre reinforced cordierite composites may constitute a promising alternative for manufacturing damage-tolerant tubular components for applications at intermediate-temperatures (up to similar to900degreesC). (C) 2002 Kluwer Academic Publishers.
Keywords: BOROSILICATE-GLASS; FABRICATION; CERAMICS; Materials Science